Propostas de melhorias na gestão de contratos da Universidade Federal de São Carlos por meio da gestão por processos - Ture, Vanessa Stevan (Universidade Federal de São Carlos, 2020)
The contracting of outsourced service companies is one of the main concerns with regard to contracts in the Public Administration, due to the complexity of monitoring and inspection, as well as because they represent high value contracts. In order to manage the execution of this type of contracting, contract management is essential to minimize the risk of damage to the public interest and damage to the treasury. Considering that the Federal University of São Carlos - UFSCar, as a federal institution of higher education, needs to have services through outsourced companies, which help in reaching the core activities, considering that UFSCar must follow all the current laws that determine and guide for a contract to be successful, as Normative Instruction n° 05/2017, which defines procedures for this type of contract and is still in the implementation phase in the institution object of this work, the present research, carried out through a study case study, it aims to contribute to improving the management and inspection of outsourced service contracts at the São Carlos campus at UFSCar through process management. For this, a mapping and analysis of the current situation of the hiring process of outsourced workers was carried out and, as a complement to the data collection, a structured interview with contract inspectors was carried out. Thus, as a product of the present work, sixteen proposals were generated with opportunities for improvement, divided into three categories: proposals related to Normative Instruction n° 05/2017, proposals generated with the interviews and proposals by the author of this work. In addition, it was possible to advance in some proposals, with the application of management tools for processes that resulted in the projection of future situations, as well as planning suggestions and models of procedures for contract management.
Improvement proposals in contract management at the Federal University of São Carlos through process management
Keywords: Gestão de contratos; Fiscalização e acompanhamento contratual; Terceirização de serviços; Gestão por processos; Administração Pública; Contract management; Contractual inspection and monitoring; Outsourcing services; Process management; Public administration; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS